Magnetite in the unequilibrated CK chondrites: Implications for metamorphism and new insights into the relationship between the CV and CK chondrites. (28th July 2016) - Dunn, Tasha L.; Gross, Juliane; Ivanova, Marina A.; Runyon, Simone E.; Bruck, Andrea M.
Abstract: Bulk isotopic and elemental compositions of CV and CK chondrites have led to the suggestion that both originate from the same asteroid. It has been argued that magnetite compositions also support this model; however, magnetite has been studied almost exclusively in the equilibrated (type 4‐6) CKs. Magnetite in seven unequilibrated CKs analyzed here is enriched in MgO, TiO2, and Al2 O3 relative to the equilibrated CKs, suggesting that magnetite compositions are affected by metamorphism. Magnetite in CKs is compositionally distinct from CVs, particularly in abundances of Cr2 O3, NiO, and TiO2 . Although there are minor similarities between CV and equilibrated CK chondrite magnetite, this is contrary to what we would expect if the CVs and CKs represent a single metamorphic sequence. CV magnetite should resemble CK3 magnetite, as both were metamorphosed to type 3 conditions. Oxygen fugacities and temperatures of CVox and CK chondrites are also difficult to reconcile using existing CV‐CK parent body models. Mineral chemistries, which eliminate issues of bulk sample heterogeneity, provide a reliable alternative to techniques that involve a small amount of sample material. CV and CK chondrite magnetite has distinct compositional differences that cannot be explained by metamorphism.